Towards institutional Mutawallis for the management of Waqf properties - Saleem, Muhammad Yusuf (2009)
This paper examines the management of waqf properties in Malaysia. Waqf comes under states’ jurisdiction and state laws are applicable to the creation, management and development of waqf properties. The institution of the Islamic Religious Council (Majlis Agama Islam) in the various states deal with the issues related to waqf including its management and act as the sole trustee (mutawalli) of all the waqf properties in the states. This paper argues that waqf as an institution is not as productive and beneficial as it was during the Islamic history. It contends that the practice of appointing government institutions as a mutawalli has not contributed to the productivity and efficient management of the waqf properties. The paper argues that in order to make waqf contribute to the socio-economic development of the Muslim communities it is essential that some changes be brought to the management of the waqf properties. The paper concludes that non-governmental institutions should be allowed to act as a trustee (mutawalli/nazir) and to manage the waqf properties for the benefit of the beneficiaries.